(untitled) (Pedagogical Horizons, 2020)
The discussion, if lessons on ethics should be taught complementary to or instead of religion in school, depends on religious political positions which regulate the relations between religion and society. Whereas a religous-integralistic approach tries to interpret and explain the whole society, a secularistic position is ready to drive out religion(s) of the public sphere of the society. On the other hand the postsecular theory is convinced that both secular and religious citizens in a pluralistic society have to learn from each other. Each of these three positions sees the question of teaching religion and/or ethics differently; this article argues for a postsecular approach which takes ethical and religious education seriously and encourages pupils to go into secular and religious sources and arguments.